Unified Tanker Survey and Inspection Regime in Terms of Reducing Psychophysical Strain of the Crew - Bielić, Toni; Hess, Mirano; Grbić, Luka (Promet - Traffic&Transportation, 2017)
The paper focuses on analysis of the effect of various surveys and inspections on the psychophysical behaviour of the crew. After analysing the scope and the extent of each regime, the authors identified more than 60% of surveys overlapping each other. Furthermore, the results of the survey conducted among seafarers indicate that the present method of carrying out ship surveys and inspections have a negative effect on the psychophysical condition of the crew. Therefore, a new method of tanker inspections has been proposed in order to reduce the psychophysical strain of the crew. The proposed method would minimise the annual duration of the inspections up to 30% and improve inspection time coordination without compromising quality and safety of the ships.